1980
DOI: 10.1007/bf02414790
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative evaluation of the effects ofAscophyllum harvesting on the littoral ecosystem

Abstract: Little is known of the ecological effects of harvesting littoral algae although this is a worldwide commercial activity. In 1976 an attempt to establish harvesting in Strangford Lough, Northern Ireland, was opposed on mainly theoretical conservation grounds. The attempt began and stopped within a single small bay leaving a sharp boundary between cut and uncut areas. A subjective survey apparently confirmed the predicted loss of cryptic fauna, decline through predation and the resorting of interboulder sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…obs.). Our results and a number of earlier studies (Knight & Parke 1950, Boaden & Dring 1980, Keser et al 1981, Keser & Larson 1984 show that both F. serratus and F. vesiculosus are capable of rapid colonisation in the mid-shore of sheltered sites in the absence of Ascophyllum. That they are absent or rare shows the competitive ability of Ascophyllum and the lack of disturbance events which could disrupt the continuous cover of Ascophyllum.…”
Section: Patch Sizessupporting
confidence: 80%
“…obs.). Our results and a number of earlier studies (Knight & Parke 1950, Boaden & Dring 1980, Keser et al 1981, Keser & Larson 1984 show that both F. serratus and F. vesiculosus are capable of rapid colonisation in the mid-shore of sheltered sites in the absence of Ascophyllum. That they are absent or rare shows the competitive ability of Ascophyllum and the lack of disturbance events which could disrupt the continuous cover of Ascophyllum.…”
Section: Patch Sizessupporting
confidence: 80%
“…Menge, 1975;Lub-manipulative experiments. It recolonizes its own zone (Burrows, 1947;Hawkins, 1979;Boaden and Dring, 1980) and sporelings were never found in various Fucus serratus removals (not all detailed here, but see Hawkins, 1979). The factors setting the lower Iimit of Ascophyllum remain unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Improper collecting techniques eliminated some populations in France and recovery was estimated to take up to 15 yr (Keser et al 1981). Removal of rockweed can also have strong negative effects on the abundance and diversity of intertidal animals (Boaden & Dring 1980). In an experiment in Maine comparing regrowth of rockweed under different collection methods (cutting at the holdfast, 15 or 25 cm from the holdfast), Keser et al (1981) found that regrowth was least in areas where plants were cut at the holdfast, especially when grazers (Littorina littorea) were present.…”
Section: Recruitmentmentioning
confidence: 99%